2011
DOI: 10.1289/ehp.1003328
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ Is a Target for Halogenated Analogs of Bisphenol A

Abstract: Background: The occurrence of halogenated analogs of the xenoestrogen bisphenol A (BPA) has been recently demonstrated both in environmental and human samples. These analogs include brominated [e.g., tetrabromobisphenol A (TBBPA)] and chlorinated [e.g., tetrachlorobisphenol A (TCBPA)] bisphenols, which are both flame retardants. Because of their structural homology with BPA, such chemicals are candidate endocrine disruptors. However, their possible target(s) within the nuclear hormone receptor superfamily has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
224
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(248 citation statements)
references
References 43 publications
21
224
3
Order By: Relevance
“…In addition, for BPAF and TBBPA, introducing a halogen into the bisphenol structure could contribute to their higher toxicities. This is because the degree of halogenation in BPA analogues could alter activation of ERs and peroxisome proliferator-activated receptors (PPARs) (Riu et al, 2011). By substituting different chemical groups and degree of halogenation, BPA and its analogues could exert differential toxicities via various receptor binding sites and binding affinities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for BPAF and TBBPA, introducing a halogen into the bisphenol structure could contribute to their higher toxicities. This is because the degree of halogenation in BPA analogues could alter activation of ERs and peroxisome proliferator-activated receptors (PPARs) (Riu et al, 2011). By substituting different chemical groups and degree of halogenation, BPA and its analogues could exert differential toxicities via various receptor binding sites and binding affinities.…”
Section: Discussionmentioning
confidence: 99%
“…It is very well documented that BPA and various related compounds bind to hormone receptors and influence multiple endocrine pathways Okada et al, 2008;Swedenborg et al, 2009;Riu et al, 2011;Soriano et al, 2012). Beyond this, recent studies provide evidence that BPA can directly interact with biologically active proteins such as enzymes and ion channels (Hiroi et al, 2006;Asano et al, 2010;Hashimoto et al, 2012;O'Reilly et al, 2012;Pandey and Deshpande, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although the two estrogen receptors (ERs), ERα and ERβ, are considered as the main targets of BPA (13,14), several other cellular targets have been proposed for this compound. We and others have previously demonstrated that BPA or its halogenated derivatives also activate the pregnane X receptor (15,16), the estrogen-related receptor γ (ERRγ) (17), or the peroxisome proliferator activated receptor γ (18,19), and inhibit the androgen receptor (AR) (20) or the thyroid hormone receptor (21,22). BPA has also been reported to interact with the G proteincoupled ER (23), so that the net effect of BPA could be caused by synergistic actions through different pathways.…”
mentioning
confidence: 99%